In vitro Cholesterol Assimilation by Bifidobacterium animalis subsp. lactis (BPL1) Probiotic Bacteria Under Intestinal Conditions - Fernández-Calderón, María C.; Sánchez-Moro, María D. H.; Rincón, Eduardo Ortega (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2022)
Background: Hypercholesterolemia is one of the principal causes of the development of cardiovascular diseases. Recently, probiotics consumption has also been proposed as a non-pharmacological intervention to control cholesterol concentrations. Objective: To evaluate in vitro assimilation of cholesterol by Bifidobacterium animalis subsp. lactis (BPL1) under simulated intestinal environment in anaerobic conditions and to review and discuss potential physiological mechanisms in this context. Methods: Bacterial viability and cholesterol assimilation were evaluated in both standard MRS and Stimulated Intestinal Fluid (SIF) medium under anaerobic conditions and in the presence or absence of cholesterol. For assimilation assays, cholesterol concentrations in the different suspensions, containing the probiotic or not, were determined by chromatography coupled to mass spectrometry. Results: The results showed that the growth of B. lactis BPL1 under intestinal conditions is favored when cholesterol is present in the culture medium. In addition, cholesterol assimilation of up to 44.4% under intestinal and anaerobic conditions was observed. Conclusion: Taking into account the revised literature and the experimental results presented herein, the administration of functional foodstuffs together with probiotic bacteria, such as B. lactis BPL1, could be a potentially effective option to decrease hypercholesterolemia, thus preventing the development of cardiovascular diseases. Nevertheless, further studies on mechanisms of effectiveness in animals and clinical trials are still needed.
Keywords: functional foodstuffs